Calcium Carbide Poisoning in a Dog - Ultrasound Findings - Ramos, Denise Jaques [UNESP]; Salazar, Diana; Yamauchi, Camila Lie; Disselli, Tamiris; de Carvalho, Kairo Adriano Ribeiro; Feliciano, Giovanna Serpa Maciel; Tinto, Stéfany Tagliatela; Pozzobon, Ricardo; Feliciano, Marcus Antônio Rossi (Universidade Federal do Rio Grande do Sul, 2023)
Background: Calcium carbide has been used not only in industry, but it is also present in the domestic environment. This substance goes through chemical reactions that lead to the release of acetylene gas and heat being capable of causing burns, damage to mucous membranes, eyes and skin, central nervous system depression and also described as an anesthetic agent. It is lethal in concentrations of 35 % for humans and 80 % for dogs. Although reports that involve this substance in animals as scarce, emergency calls related to intoxication are part of the small animal clinical routine. This report aims to describe laboratory and ultrasonography findings in a case of carbide poisoning in a dog. Case: A 8-year-old American Staffordshire Terrier with a history of emesis, bloody diarrhea, hiporexy, oligodipsy and ingestion of calcium carbide for 3 days was admitted for medical care at the University Veterinary Hospital of Universidade Federal de Santa Maria (UFSM). The patient had a previous diagnosis of hypoadrenocorticism which was treated with sodium liothyronine 800 mg prescribed by another professional and whose dose was reduced to 600 mg by the owner without veterinary indication. Physical examination showed a high body score, evident lameness of the hind limbs, hyperemic mucosa with elevated time of capillary perfusion and an increase of mandibular and popliteal lymph nodes. Dehydration, fever, elevated heart and respiratory rates and skin lesions of the front limbs were also noted. The main possible differentiate diagnosis based on these clinical signs and history presented by the patient were poisoning calcium carbide intoxication, diabetes mellitus and hypoadrenocorticism. The dog was hospitalized to receive initial treatment and undergo further examination The first treatment instituted was dipyrone [Dipyrone Ibasa 50%® - 15 mg/kg, i.v, TID, for 3 days], tramadol hydrochloride [3 mL/kg, i.v, TID, for 2 days], sucralfate [Sucrafilm® - 5 mg/mL, v.o, TID, for 2 days], maropitant citrate [Cerenia® - 0.1 mg/kg, sc, SID, for 3 days], omeprazole [1 mg/kg, i.v, SID, for 3 days], levothyroxine [300 mg, ½ (half) tablet, v.o, BID, for 2 days]. Blood results have shown leukocytosis (19,600; reference 5,700-14,200) e lymphopenia (196/µL; reference 900/µL-4,700/µL) and in the biochemical tests, there was an increase in triglycerides (175 mg/L; reference 23 mg/L-102 mg/L), without signs of renal or hepatic lesions. In the ultrasonography exam, hepatomegaly and splenomegaly with a heterogeneous parenchyma were noticed. Alteration of the gastrointestinal tract with a thickened wall was also noticed associated with gas in the digestive tract and hyperechoic area in mucous layer. These findings are compatible with reports of mucosal irritation associated with this substance. The pancreas parenchyma was slightly heterogeneous and hyperechoic with enlargement of the body and small disperse hyperechoic focuses. Left adrenal images were compatible with clinical suspicions of hyperadrenocorticism. Discussion: All the alterations found in the imaging exam were compatible with the clinical signs due to direct contact with the substance in question. Dystrophic mineralization focuses found in spleen and pancreas can be due to the alterations of phosphorus and calcium even if not described in literature associated with calcium carbide poisoning. In conclusion, the clinical signs presented, and the image findings of this patient confirmed the danger and potentially lethal effects of the contact and ingestion of calcium carbide. The literature about this subject is scarce and deeply in need of more attention associated with new measures for prevention, instruction to owners and development of diagnose and treatment emergency protocols of these animals.
Keywords: dog; intoxication; toxicity; ultrasonography